Review of methods for planning the scope of medical care and financing of the healthcare system by the subjects of the Russian Federation - S. A. Kovaleva; D. V. Fedyaev; N. N. Sisigina (Фармакоэкономика)
The article presents a review of current and alternative methods for planning the scope and financing of medical care in the subjects of the Russian Federation. The relevance of the issue is due to the imperfection of the current planning model, which stimulate representatives of the profile bodies and independent experts to develop alternative methods. The current approaches and legal documents regulating the procedure for distributing the scope of medical care and financial resources to pay for this care are discribed. The analysis of alternative methods shows how different demographic and infrastructural features of regions can be used to redistribute the scope of medical care and the corresponding financial support.